Implementation of the Problem-Based Learning Model to Improve Student Learning Outcomes on Green Chemistry Material in E Phase MAS MTI Batang Kabung, Padang City - Tri Putri Wahyuni; Dian Permata Sari (Science Journal Get Press, 2024)
This study investigates the efficacy of problem-based learning (PBL) in enhancing student learning outcomes in Green Chemistry at MAS MTI Batang Kabung, Padang City. The research addresses the prevalent use of conventional teaching methods, which have resulted in low student engagement and academic performance. A classroom action research design, based on Kemmis and McTaggart's model, was employed. The study population comprised Grade X Phase E students from the 2023/2024 academic year, with a sample drawn from classes X.1 and X.2. Data collection methods included observation, questionnaires, documentation, and field notes. Analysis of learning outcomes utilized percentage techniques and t-tests. The implementation of PBL showed significant improvement in student learning outcomes. Average scores increased from 71.61% in the first cycle to 86.96% in the second cycle. These results demonstrate that PBL effectively enhances student performance in Green Chemistry education at MAS MTI Batang Kabung. This research contributes to the growing body of evidence supporting the use of active learning strategies in chemistry education, particularly in the Indonesian context. The findings suggest that wider adoption of PBL could lead to improved educational outcomes in similar settings.